Seasonal baseline of nutrients and stable isotopes in a saline lake of Argentina: biogeochemical processes and river runoff effects - Kopprio, Germán Adolfo (2014)
The seasonal variability of inorganic and organic nutrients and stable isotopes and their relations with plankton and environmental conditions were monitored in Lake Chasicó. Principal component analysis evidenced the strong influence of the river runoff on several biogeochemical variables. Silicate concentrations were controlled by diatom biomass and river discharge. Higher values of nitrate and soluble reactive phosphorus (SRP) indicated agricultural uses in the river basin. Elevated pH values (∼9) inhibiting nitrification in the lake explained partially the dominance of ammonium: ∼83 % of dissolved inorganic nitrogen (DIN). The low DIN/ SRP ratio inferred nitrogen limitation, although the hypotheses of iron and CO2 limitation are relevant in alkaline lakes. Particulate organic matter (POM) and dissolved organic matter (DOM) were mainly of autochthonous origin. The main allochthonous input was imported by the river as POM owning to the arid conditions. Dissolved organic carbon was likely top-down regulated by the bacterioplankton grazer Brachionus plicatilis. The δ13C signature was a good indicator of primary production and its values were influenced probably by CO2 limitation. The δ15N did not evidence nitrogen fixation and suggested the effects of anthropogenic activities. The preservation of a good water quality in the lake is crucial for resource management.